The role of VEGF and its soluble receptor VEGFR-1 in preterm newborns of preeclamptic mothers with RDS. (July 2013) - Kalay, Salih; Cakcak, Burak; Oztekin, Osman; Tezel, Gonul; Tosun, Ozgur; Akcakus, Mustafa; Oygur, Nihal
Abstract Objective: We measured vascular endothelial growth factor (VEGF) and soluble VEGF receptor 1(sVEGFR-1) concentrations in cord blood and tracheal aspirate fluid (TAF) in order to investigate the role of them in lung maturation and the severity of respiratory distress syndrome (RDS) in preterm newborns, born to preeclamptic mothers. Methods: Newborns were divided into two groups as preterms born to preeclamptic mothers and preterms born to healthy mothers. They were also divided into two groups as severe RDS (sRDS) and mild RDS (mRDS) according to the need of surfactant and extent or type of ventilatory support. The concentrations of VEGF and sVEGFR-1 in cord blood and TAF (only in preterms with sRDS) were assayed by standardized enzyme-linked immunosorbent assay. Results: When the patients were evaluated as sRDS and mRDS, cord blood VEGF and VEGF/sVEGFR-1 concentrations of preterms with sRDS were significantly lower than the concentrations of preterms with mRDS. Conversely, cord blood sVEGFR-1 concentrations of preterms with sRDS were significantly higher than the concentrations of preterms with mRDS. VEGF and sVEGFR-1 concentrations in TAF could be compared only between sRDS preterms, born to preeclampsia (+) and (−) mothers. No statistical significance was detected between the two groups when sVEGFR-1, VEGF and VEGF/sVEGFR-1 concentrations in TAF were compared. Conclusion: Preeclampsia seems not to have an important effect on VEGF and sVEGFR-1 concentrations of preterm newborns both in cord blood and in TAF. Low VEGF and high sVEGFR-1 concentrations seem to be associated with the severity of RDS irrespective of preeclampsia, suggesting that VEGF may be one of the main components of lung maturation.